Commercialization of Sago through Estate Plantation Scheme in Sarawak: The Way Forward. (27th October 2016) - Mohamad Naim, Hafizan; Yaakub, Ahmad Nizar; Awang Hamdan, Dayang Asmah
Abstract : Sago has been hailed as a next viable commodity in Sarawak, Malaysia, given its potential as a versatile crop. Realising its potential, Sarawak state government has started initiatives to stimulate sago plantation from subsistence farming to estate plantation. The move of introducing sago estate plantation is a bold one considering that Malaysia is the first country introducing such plantation design. This is a reflection on sago estate plantation in the state of Sarawak. It is observed that, in order to ensure success of the plantation scheme, factors such as rigorous land consolidation programme aiming to maximize sago production; introduction of a modern planting method that integrates well with the traditional planting method; rigorous scientific research in finding the best sago variety that produces high yield; effective communication between related agencies and smallholders; and concentrated involvement of all actors, governmental agencies, mills, and smallholders, have to be addressed accordingly. To conclude, it is hoped that this writing can be utilized as part of a contribution to accelerating commercialization of sago as a next viable commodity crop not only in Sarawak but in Southeast Asia as a whole.